Cost Accounting in the CPA Examination–Updated . - Usry, Milton F.; Tracy, John A. (The Accounting Review, 1971)
Abstract This paper summarizes the extent and types of coverage of cost accounting topics in the ten CPA exams during 1966-1970 inclusive. Comparisons are made to my earlier study covering the period 1956-1965.